Molecular docking of immunogenic peptide of Toxoplasma gondii and encapsulation with polymer as vaccine candidate - Cakir-Koc, Rabia; Budama-Kilinc, Yasemin; Kokcu, Yagmur; Kecel-Gunduz, Serda (TAYLOR & FRANCIS LTD, 2018)
Toxoplasma gondii is one of the most widely spread parasitic organisms in the world. T. gondii causes primary, chronic infection and mortality. Major surface antigen 1 is the most abundant tachyzoite surface protein and highly conserved between species and causes strong humoural response. Some studies showed that the peptide sequence of surface antigen has immunity. Therefore, tachyzoite surface antigenic peptide sequence is one of the good candidates for vaccine development. However, conformational information and delivery systems are very important parameters for vaccine development. Computational chemistry which is used as an effective method to perform drug or vaccine design provides important information on structure-activity relationship, biological effects of functional groups, molecular geometry, design of enzyme inhibitors and antagonists. The interaction of immunological peptides with protein systems was carried out by means of computing the free energy of binding using the molecular docking technique. Due to the major histocompatibility complex (MHC), proteins play a substantial role for adaptive immunity, the crystal structure of a MHC class I, which plays a pivotal role in the adaptive branch of the immune system, was preferred for docking calculations. A delivery system based on poly(lactic-co-glycolic acid) (PLGA) nanoparticles and peptide loaded PLGA nanoparticles was prepared in this study to improve the bioavailability of tachyzoite surface antigenic peptide sequence. Double emulsion method (water-in-oil-in-water or w/o/w) was used for synthesis of PLGA and peptide loaded PLGA nanoparticles. The average particle size, polydispersity index and zeta potential values of PLGA and peptide loaded PLGA nanoparticles were measured with zeta-sizer by using dynamic light scattering (DLS) technique. The scanning electron microscope (SEM) (Zeiss Supra 50 V) was used for imagining the peptide loaded PLGA nanoparticles. Cell toxicity of nanoparticles was assayed on AGS (gastric adenocarcinoma) cell line. To evaluate mitochondrial activity of cells and toxicity studies, XTT methods were carried out. In this study, we aimed to obtain specific immunological peptide loaded PLGA nanoparticles and characterize the formation with FTIR, zeta sizer and SEM imaging, and evaluate cytotoxicity and carry out molecular docking calculations of peptide-MHC protein in order to enlight in vivo events as vaccine candidate against T. gondii.
Keywords: Toxoplasma; cytotoxicity; PLGA; XTT; SEM; molecular docking; ANTIGENS; CANCER; Biotechnology & Applied Microbiology; Engineering; Materials Science